Environmental sanitation practices in Osogbo, Nigeria: An assessment of residents' sprucing-up of their living environment - Oluwole Daramola; Oluwaseun Olowoporoku (Economic and Environmental Studies (E&ES), 2016)
This paper examined residents' environmental sanitation practices across different residential zones of Osogbo, Nigeria. The stratified residential zones are the traditional zone, the transition zone and the sub-urban zone. A total of 194 residents were selected for survey using systematically sampling technique. The study revealed that residents' socio-economic characteristics varied significantly with different residential zones. Findings revealed that there is low level of access to environmental sanitation facilities across the residential zones. Similarly, the proportion of residents' with environmental sanitation facilities in their homes was low. The study established poor environmental sanitation practices among the residents in terms of utilization of available amenities across the residential zones. It recommended the provision of environmental sanitation facilities in homes by residents and communal provision of facilities by government and Community Based Organizations (CBOs), environmental education and also the enforcement of environmental regulations in the city and others with similar setting.
Keywords: D19; K32; 330; environment; environmental sanitation; practices; residents' Osogbo; Africa